The value of echocardiographic examination in predicting right ventricular heart failure in patients after the implantation of continuous-flow left ventricular assist devices. (20th November 2018) - Paluszkiewicz, Lech; Börgermann, Jochen
Abstract: The number of implanted left ventricular assist devices is increasing systematically. Novel systems are being introduced and survival rates are improving, but complications, such as heart failure, leading to high early and late mortality still exist. Echocardiography is the preferred method for assessing the anatomy and function of the right ventricle (RV). In spite of the many methods available for use, including 2- and 3-dimensional techniques, assessment of the RV remains challenging. In this review, we present echocardiographic parameters that are most often used to assess right ventricular anatomy and function, and analyse their ability to predict right heart failure after the implantation of a left ventricular assist device.